The Development of a Local History Module on Cross-Cultural Interactions in Malay Society in South Sumatera Based on Authentic Assessment - Eva Dina Chairunisa; Muhamad Idris; Kiki Aryaningrum (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
This study aims to develop a local history on the topic of Malay Cross-Cultural Interaction in South Sumatra Based on Authentic Assessment as a contextual learning resource for senior high school students. The study is motivated by the limited availability of local history teaching materials that are not yet equipped with operational authentic assessment instrumens for classroom implementation. This research employed a research anda development (R&D) approach using the ADDIES model (Analyze, Design, Implement Evaluate). The analyze phase involved a learning needs analysis and a review of local historical sources. The design phase included the development of the module structure, performance tas design, assessment instrumens, and scoring rubrics. The develop phase produced a prototype module thar was validated through expert judgement by subject-matter experts in history, history education ecperts and educational assessment experts. The implement phase was conducted through a limited a trial involving 35 tenth-grade senior high school students to assess the readability anda practically od module. The evaluate phase consisted of revisions bades on the trial result. Data were analyzed descriptively using both qualitatibe and quantitative methods, employing Aiken’s V index and practically percentage analysis. The validation results indicate that the authentic assessment instrument achieved a very high validity level with an Aiken’s Value od 0,89, while the limited trial results showed a practically level 89,38% with positive student responses.